The Use of Unconventional Malts in Beer Production and Their Effect on the Wort Viscosity - Blšáková, Lucia; Gregor, Tomáš; Mešťánek, Matej; Hřivna, Luděk; Kumbár, Vojtěch (Foods (Basel, Switzerland), 2021)
The aim of this study was to use unconventional malts in beer production and observe their effect on the wort viscosity. Six malts were analysed in this study-barley, black barley, oat, wheat, rye, and corn. Firstly, the parameters of cereals were measured after the malting process in an experimental malting house and wort production. Samples were analysed in each phase of the mashing process. Carbohydrate contents and viscosities were analytically determined from the samples. The resulting values of the dynamic viscosity were significantly higher than the values obtained by other authors, ranging from 3.4 up to 35.5 mPa·s-1. This study also confirmed the hypothesis that states that the breakdown of carbohydrates leads to a decrease in viscosity. Values measured in the black barley malt sample were higher when compared with light barley malt. Unconventional malts had a higher viscosity and were thus more difficult to filter. If these types of malts are used it is recommended to add barley malts or malts with a higher enzyme activity to them.
Keywords: viscosity; beer production phases; beer; malt; wort